Análise da competitividade das exportações de pimenta-do-reino do Pará e do Brasil no período de 1997 A 2007 eperspectivas de comércio - Câmara, Juliano João Romcy (2010)
Brazil and particularly the state of Pará is increasing considerably its export values of black and white pepper and thus generating income for the country. However, little is known about the degree of competitiveness in the state of Pará in relation to other producing states as well as the degree of competitiveness of Brazil in relation to other producing countries. To understand this better we sought to identify the competitive performance of the state of Pará relative to the other producing states of Brazil and consequently in relation to its competitors in this segment. To achieve this proposal were outlined the following objectives: To analyze the competitiveness of black and white pepper from Pará and Brazil in the period between 1997 to 2007 and present the main conclusions and trade prospects. The analysis was based on the concept of competitiveness understood as: The ability of a company or country to stay in business through a competitive position created for a product or product group, and that the fruit of its strategies are capable of effectively maintaining or increasing efficiently its competitive position in the international market. The methodology used was based on descriptive tabular analysis and index calculation of export performance: Revealed Comparative Advantage (VCR); Coverage Rate (TC) Trade Intensity (IC) and Position in the World Market (Sik). The results showed that the state of Pará and the country as a whole were competitive in the international trade of black and white pepper during the period under investigation with the VCR and the TC above the standard index, indicating efficiency and commercial dynamism. The analysis of the Trade Intensity Index (IC) showed that the major trends in bilateral trade in the state of Pará were, in order of importance; Argentina, Mexico and Spain while for Brazil as a whole, also in order of importance were; Argentina, Spain and Mexico. According to the Position in the World Market index (Sik), it was found that only Vietnam and Brazil had market share gains throughout the entire period under study. Although Vietnam has absorbed much of the global market share over the last ten years, Brazil has also gained a small part of that market, which leads us to believe that with the adoption of technologies for quality production of black and white pepper together with the development of a systematic marketing plan, Brazil will ultimately become more competitive and will therefore be able to considerably expand its participation in international trade in this product.